Frequent HPV-independent p16/INK4A overexpression in head and neck cancer. (August 2018) - Lechner, Matt; Chakravarthy, Ankur R.; Walter, Vonn; Masterson, Liam; Feber, Andrew; Jay, Amrita; Weinberger, Paul M.; McIndoe, Richard A.; Forde, Cillian T.; Chester, Kerry; Kalavrezos, Nicholas; O'Flynn, Paul; et al.
Highlights: HPV status will play an increasingly important role in the management of HNSCC. p16 INK4A (p16) is routinely used as the biomarker for diagnosis of HPV(+) HNSCC. p16 INK4A (p16) is frequently upregulated in HPV(−) non-oropharyngeal HNSCC. Tumours with high levels of wild-type p16 are enriched for mutations in NSD1. Alternative HPV biomarkers are required for HPV-driven non-oropharyngeal HNSCC. Abstract: Objectives: p16 INK4A (p16) is the most widely used clinical biomarker for Human Papillomavirus (HPV) in head and neck squamous cell cancer (HNSCC). HPV is a favourable prognostic marker in HNSCC and is used for patient stratification. While p16 is a relatively accurate marker for HPV within the oropharynx, recent reports suggest it may be unsuitable for use in other HNSCC subsites, where a smaller proportion of tumors are HPV-driven. Materials and methods: We integrated reverse phase protein array (RPPA) data for p16 with HPV status based on detection of viral transcripts by RNA-seq in a set of 210 HNSCCs profiled by The Cancer Genome Atlas project. Samples were queried for alterations in CDKN2A, and other pathway genes to investigate possible drivers of p16 expression. Results: While p16 levels as measured by RPPA were significantly different by HPV status, there were multiple HPV (−) samples with similar expression levels of p16 to HPV (+) samples, particularly at non-oropharyngeal subsites. In many cases, p16 overexpression in HPV (−) tumors could not be explained by mutation or amplification of CDKN2A or by RB1 mutation. Instead, we observed enrichment for inactivating mutations in the histone H3 lysine 36 methyltransferase, NSD1 in HPV (−)/p16-high tumors. Conclusions: RPPA data suggest high p16 protein expression in many HPV (−) non-oropharyngeal HNSCCs, limiting its potential utility as an HPV biomarker outside of the oropharynx. HPV-independent overexpression of wild-type p16 in non-oropharyngeal HNSCC may be linked to global deregulation of chromatin state by inactivating mutations in NSD1 .